Iowa Birdline update, December 16, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of Iowa Birdline updates for December 16, 1991. The highlights for the update include the sighting a Marbled Murrelet, Glaucous Gulls including two first year birds, and a first year Thayer's Gull. Also included are handwritten notes with sightings of a Common Redpoll, White-winged Crossbill, Snow Bunting, Long and Short-eared Owls and twelve Eurasian Tree Sparrows. Epson - sheet feed/flatbed